New advances in the science and use of Trichoderma spp. - Gary Harman (浙江大学学报. 农业与生命科学版)
Trichoderma spp. have been known for their strong abilities to produce extracellular enzymes, especially cellulases and glucanases by T. reesei, and also for their abilities to control plant pathogens. Most notably, a number of lines of evidence indicate that the agriculturally relevant strains are synergistic plant symbionts. As plant symbionts they possess the following characteristics: (a) they infect plant roots but cause the plant to restrict their growth to outer layers of the plant cortex (an exception is the recent discoveries of plant endophytic strains of Trichoderma and Gliocladium), (b) they produce bioactive plant molecules in the zone of interaction that (c) induce localized systemic resistance to plant diseases and (d) systemic plant resistance to diseases that in some respects is similar to that induced by rhizobacteria, (e) they induce changes in plant proteomes, (f) increase plant growth and yield at least in part by enhancing root growth, and (g) they increase plant nutrient uptake. The increase in plant growth and yields is strongly interactive with plant genotype, at least in maize. There also are very significant increases in the knowledge of events that occur in mycoparasitism that in many respects have features in common with their interactions with plants. They are highly resistant to toxicants and have recently been shown to degrade cyanide and take up, and then degrade, metallocyanides. These discoveries allow new uses for the organisms in managed plant systems, including agriculture. For example, the induced systemic resistance system allows control of fungi, bacteria, Oomycetes and even one virus at sites temporally and spatially distant from the site of application. The abilities of the fungi to resist/degrade toxicants and increase plant growth indicate they will highly useful components in plant-microbe or microbe-only strategies for remediation of soil and water pollution. Finally, there are new uses of their enzyme systems for production of chitin degradation products for use as nutraceuticals or pharmaceuticals.